LIFE CYCLE OF THE LARGE SALMON ARAB BUTTERFLY COLOTIS FAUSTA (LEPIDOPTERA: RHOPALOCERA: PIERIDAE - S. APPALA NAIDU; S. P. VENKATA RAMANA (The Bioscan, 2010)
The life cycle of the large salmon arab Colotis fausta from Eastern ghats of India was investigated. The population index of eggs, larvae and pupae on the host plant Cadaba fruiticosa was recorded. The number of broods yearly was estimated i.e., from 10-12. Life cycle from egg to adult emergence was spanning over 19- 26 days.